Distinguishing pain profiles among individuals with long COVID - Tabacof, Laura; Chiplunkar, Maanas; Canori, Alexandra; Howard, Rebecca; Wood, Jamie; Proal, Amy; Putrino, David (Frontiers in Rehabilitation Sciences, 2024)
BackgroundFor many people with long COVID (LC), new-onset pain is a debilitating consequence. This study examined the nature of new-onset pain and concomitant symptoms in patients with LC to infer mechanisms of pain from the relationships between pain and health-related factors.MethodsPain and other symptoms were evaluated in 153 individuals with LC using the Self-Administered Leeds Assessment of Neuropathic Symptoms and Signs, EuroQoL Visual Analog Scale, and Quality of Life in Neurological Disorders. The relationships between pain and patient factors were analyzed using Chi Square and independent t-tests.Results20.3% of individuals who reported new-onset pain had neuropathic pain, which was associated with lower quality of life and higher rates of cognitive dysfunction compared to those with non-neuropathic pain. Other symptoms were similar between groups, however heart-related symptoms were more prevalent in individuals with neuropathic pain and mood swings were more prevalent for individuals with non-neuropathic pain.ConclusionsCharacterizing the relationships between NP and quality of life in individuals with LC can aid in developing better clinical management strategies. Understanding the associations between NP and cognitive dysfunction provides the imperative foundation for future studies further examining the pathophysiological mechanisms underlying pain development in LC.